Molecular basis of antibiotic self-resistance in a bee larvae pathogen - Tam Dang; Bernhard Loll; Sebastian Müller; Ranko Skobalj; Julia Ebeling; Timur Bulatov; Sebastian Gensel; Josefine Göbel; Markus C. Wahl; Elke Genersch; Andi Mainz; Roderich D. Süssmuth (Nature Communications, 2022)
The authors show that the N-acetyltransferase PamZ acts as a self-resistance factor disabling the antibacterial paenilamicin that is produced by the honey bee larvae pathogen Paenibacillus larvae.